COMPUTER-ASSISTED SPERM ANALYSIS OF SPERM MOTILITY DYNAMICS IN GAGA ROOSTERS AT DIFFERENT AGES - Khaeruddin, Khaeruddin; Sawitri, Wiwied; Junaedi, Junaedi (Jurnal Kedokteran Hewan, 2025)
This study aimed to evaluate the motility and kinematic parameters of Gaga chicken sperm at different ages using Computer-Assisted Sperm Analysis (CASA). Semen samples were collected seven times each from two roosters aged 6 months (young) and 12 months (mature) using the massage method. CASA evaluation assessed multiple parameters total motility, progressive motility, slow, static, distance average path (DAP), distance straight line(DSL), distance curvilinear (DCL), velocity average path (VAP), velocity straight line (VSL), velocity curvilinear (VCL), straightness (STR), linearity (LIN), amplitude of lateral head displacement (ALH), beat cross frequency (BCF), and wobble (WOB). Data were analyzed using an independent samples t-test. The results showed significant differences (P0.05) in progressive motility, DCL, VAP, and VCL between the two age groups, with the 12-month-old rooster showing higher values compared to the 6-month-old. In conclusion, the significantly higher sperm concentration and viability observed in mature roosters in this study underscore the importance of age-related reproductive maturity in optimizing semen quality for breeding purposes.